60 Yarning, giving a voice to older aboriginal people on healthy ageing and fall prevention. (1st September 2016) - Coombes, J; Lukaszyk, C; Keay, L; Sherrington, C; Tiedemann, A; Ivers, R
Abstract : Background: There is emerging evidence that falls are an increasing problem for older Aboriginal people in Australia. We examined concepts of healthy ageing and fall prevention using Aboriginal ontology and knowledge systems through yarning circles in Aboriginal communities in Australia. Methods: We used a conversational method to gather knowledge through yarning circles with Aboriginal communities in the Central Coast, Dubbo, Mt Druitt and Shoalhaven areas of New South Wales, Australia. The yarning circles were held with 80 people aged from 45 to 85 years of age, in 8 groups between November 2014 and April 2015. Data were audio recorded and transcribed with the consent of communities and analysed using an Indigenous research standpoint methodology, incorporating ways of knowing, doing and being. Results: Yarning circles helped identify key issues around healthy ageing including the role of falls, in particular the impact these have on individuals, their families and communities. Discussions around falls highlighted concerns that they would lead to an inability to fulfil family roles or remain involved in community life. Participants reported that healthy ageing and maintaining independence were imperative in enabling them to continue to pass on cultural knowledge, and that they were comfortable attending health-related programs in their own communities. Conclusions: Aboriginal people felt comfortable attending programs in their own community and yarning circle participants voiced strongly that healthy ageing is essential for them to continue to share their knowledge of Aboriginal history and culture to their families and communities. Yarning circles also identified the need for Aboriginal-specific, culturally appropriate fall prevention programs to address healthy ageing and concerns about falls.